Manajemen Peningkatan Kompetensi Pedagogik Guru dalam Implementasi Kurikulum Merdeka di SMA Negeri 2 Brebes Kabupaten Brebes - Arifin, Desi Lina; Bunyamin, Bunyamin; Nugrahani, Dyah (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Research results (a) planning to increase teachers' pedagogical competence in implementing the independent curriculum at SMA Negeri 2 Brebes include 1) formulating a vision and mission, 2) analyzing teacher needs, 3) setting goals for increasing pedagogical competence, 4) preparing plans and 5 ) program to increase pedagogical competence and determine the type of activity; (b) the work program for increasing teacher pedagogical competence in implementing the independent curriculum at SMA Negeri 2 Brebes is 1) understanding the independent curriculum, 2) teachers implementing the independent curriculum in classroom learning activities, 3) teachers developing designs in developing teaching modules and 4) teachers developing designs for assessment instruments; (c) The strategy for increasing teacher pedagogical competence in implementing the independent curriculum at SMA Negeri 2 Brebes includes conducting a program evaluation so that we can know what needs to be done in the future based on the results of the evaluation. Then determine the strategy and identify supporting and inhibiting factors. Conclusion: Independent curriculum management in improving teachers' pedagogical competence at the planning stage, program implementation and strategies for increasing pedagogical competence are carried out with existing procedures and provisions, implementation involves all school components.